Parametric study on process parameters of FDM 3D printer for thermoplastic materials. (2022) - Kumar Mawandiya, Bimal; Pancholi, Kushal; Shah, Dhaval B.; Joshi, Shashikant J.
Abstract: Subtractive processes of manufacturing require lots of processes for fine woks, followed up by casting, machining, grinding etc. The subtractive processes are particularly suited for mass production and for small batch production, they are too much expensive and sum up by waste of resources. 3-D printing provides an option by providing additive manufacturing process, so that any piece of material in today fast growing world can be manufactured easily and economically. The main aim of the work presented is to study the different parameters of 3-D printed materials, so that it can be used whenever needed with correct details. As an input parameters the authors have examined resolution, print strength and print pattern while as an output parameters different tests like tensile test, impact test, absorption test, porosity measurement test and di-electric strength measurement are being carried out. Based on the results of the tests, explicitly it can be concluded that specific input parameters are the best combination that should be fixed for particular applications.